Impact of Obesity on Pregnancy Outcome in Different Ethnic Groups: Calculating Population Attributable Fractions - Oteng-Ntim, Eugene (Public Library of Science, 2013)
OBJECTIVES: To quantify the proportion of adverse pregnancy outcome attributable to maternal obesity. DESIGN: Cross sectional analysis of routine obstetric dataset. SETTING: Guy’s and St Thomas’s NHS Foundation Trust (GSTFT). POPULATION: 23,668 women who had singleton deliveries at GSTFT between 2004 and 2008. METHODS: Logistic regression was used to estimate the association between BMI and outcome in different ethnic groups. Adjusted odds ratios, and the proportions of obese women, were used to calculate population attributable risk fractions (PAFs). MAIN OUTCOME MEASURES: (i) Maternal outcomes: diabetes, type of delivery, post-partum haemorrhage, and preterm delivery. (ii) Perinatal outcomes: macrosomia, low birth weight, admission to neonatal intensive care/special care baby unit, and perinatal death. RESULTS: The prevalence of maternal obesity was 14%. Increasing BMI was independently associated with increasing risk of adverse obstetric and neonatal outcome. At the individual level, the effect of obesity on diabetes was highest in Asian women compared to white women (p for interaction = 0.03). Calculation of population attributable risk fractions demonstrated that one third of diabetes cases and one in six Caesarean sections could be avoided in this population if all obese women were of normal BMI. At the population level, the contribution of obesity to diabetes was highest for Black women (42%), and lowest for oriental women (8%). Seven percent of neonatal macrosomia in all the population, and 13% in Black mothers, were attributable to obesity. CONCLUSIONS: Preventing obesity prior to pregnancy will substantially reduce the burden of obstetric and neonatal morbidity in this population. This reduction will be higher in Black women.